Challenges in the Implementation of CLIL in Higher Education: From ESP to CLIL in the Tourism Classroom - Melita Vanessa Vega; Maria de Lourdes Moscoso (Universidad de La Sabana, 2019)
Retos en la implementación de CLIL en la educación superior: de ESP a CLIL en el aula de turismo Desafios na implementação do método AICL no ensino superior: do ESP à AICL na sala de aula de turismo Content and Language Integrated Learning (CLIL) has often been touted as an effective means of enhancing the language proficiency gains among its learners due to its focus on content over form and higher cognitive demand. However, cautions have been raised regarding the varying conditions and contexts that need to be taken into consideration in order to ensure its effectiveness. This study aimed to analyze the outcome of switching from an English for Specific Purposes (ESP) program to a CLIL program in the fourth and fifth semesters of the School of Tourism at the University of Azuay. Study participants were randomly divided into two groups: a CLIL (experimental) and a non-CLIL group (control), where the former received CLIL instruction and the latter received ESP instruction for an average of five hours per week over a period of two consecutive semesters. The findings revealed no significant increases in language proficiency or differences in achievement between the two groups, thus suggesting that the starting language level of learners influenced the results of the CLIL program. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Vega, M. V. & Moscoso, M. L. (2019). Challenges in the Implementation of CLIL in Higher Education: From ESP to CLIL in the Tourism Classroom. LACLIL, 12(1), 144-176. DOI: https://doi.org/10.5294/laclil.2019.12.1.7 Received: 24/04/2019 Approved: 03/10/2019